New Insight Into the Molting and Growth in Crustaceans: Regulation of Energy Homeostasis Through the Lipid Nutrition - Yuan, Ye; Jin, Min; Fang, Fang; Tocher, Douglas R.; Betancor, Mónica B.; Jiao, Lefei; Hong, Yucong; Zhou, Qicun (Frontiers in Marine Science, 2022)
Organisms can regulate mitochondrial metabolic adaptation, further ameliorate the energy homeostasis to control the ATP production for the energy expenditure during the growth process under different physiological and nutritional conditions. Based on this understanding, the objective of the present study was to investigate how different dietary n-3 PUFA (polyunsaturated fatty acid) lipid sources modify the mitochondrial metabolic adaptation, and further affect the energy homeostasis and the growth of swimming crab (Portunus trituberculatus). A total of 120 swimming crab juveniles with an average initial weight of 10.17 ± 0.12 g were fed one of three diets (4 replicates/treatment) containing either fish oil (control), krill oil or linseed oil as dietary lipid sources for 8 weeks, and the effects of dietary lipid sources on the growth and energy homeostasis via the regulation of mitochondrial metabolic adaptation were evaluated. The study revealed that, compared with linseed oil rich in 18:3n-3, fish oil and krill oil rich in 20:5n-3 and 22:6n-3 significantly promoted the molting and growth of juvenile swimming crab, increased the ATP level, mitochondrial membrane potential, NAD+ substrate level, NAD+/NADH ratio and the mitochondrial DNA copy number. Furthermore, crabs fed the diet supplemented with krill oil can up-regulate the expression levels of genes related to energy metabolism. In addition, dietary krill oil also specifically improved the ability for scavenging free radicals produced in the process of physiological metabolism, reduced the level of lipid peroxidation and the degree of DNA oxidative damage, and improved the health status of swimming crab. The present study revealed the adaptation of mitochondrial metabolism and the regulation of the energy homeostasis of swimming crab to different dietary n-3 PUFA lipid sources, and provided a new insight into the relationship between the growth as well as molting and the energy homeostasis, which provided a novel insight into the lipid nutrition and energy metabolism of crustacean species.